Mutual Shocks of Real Effective Exchange Rate and Remittances in Ukrainian Economy - Ihor Oleksiv; Diana Mirzoieva; Roman Shulyar; Halyna Mykhailiak (LEMA) (Communications of International Proceedings, 2020)
Current paper concentrates on research of exchange rate shocks of Ukrainian hryvnia caused by inflows of remittances and vice versa in 1996-2019. We employed VAR model and found that real exchange rate (REER) is affected by values of itself and remittances with one-lag delay, which led to appreciation of REER. At the same time, remittances are affected only by its values with one-, two- and three-lag delays. Impulse response functions showed that positive shock in remittances leads to rapid appreciation of REER in one quarter. Finally, positive shock in REER causes increase in remittances in first two quarters.
Keywords: Remittances; Real Effective Exchange Rate (REER); Impulse Response Function.